RESEARCH ON KINEMATIC CALIBRATION METHOD OF THREE DEGREE OF FREEDOM SERIES MANIPULATOR BASED ON BALLBAR - CHE YaXiao; YANG XinGang; GAO Feng; HUANG YuMei; HAN WenTao; GAO Heng (Jixie qiangdu)
Considering geometry structure characteristics of the manipulator being calibrated and using modified 5-parameter method to describe its geometric patameter errors,an end position error model of the manipulator is proposed. After the zero position calibration of the manipulator,measurement data used in calibration process is obtained by one time ballbar installation.An error identification model is built based on the geometric constraints of closed kinematic chain—composed of the manipulator and ballbar as well as the end position error model,then the manipulator geometric parameters errors are calculated using nonlinear least square iterative method. A calibration experiment is completed,and the errors of the manipulator are compensated by integrated error compensation method. Along two given test end point paths,the ballbar length variation decreased from0. 395 mm,0. 456 mm to 0. 005 mm,0. 010 mm respectively before and after calibration. The research shows that the calibration method is effective and correct,and the position accuracy of the manipulator is improved.